PENGARUH KUALITAS PRODUK DAN IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN ISOTONIK POCARI SWEAT DI KOTA PONTIANAK - admin, Afrian Dwi Nugraha B11110121 (Jurnal Manajemen Update, 2017)
This study aims to examine and analyze the effect of the quality of products and of television advertising on purchasing decisions. This research uses a causal research design. The population in this study is that consumers who have purchased and consumed isotonic drink in Pontianak. This research uses accidental sampling with a sample size of 100 people. The analysis technique used is multiple linear regression analysis using SPSS version 20.0. Based on the due diligence performed models showed the model in this study deserves to be tested. Results of the analysis showed that the variable drive quality product does not have a significant influence on the purchase decision variable isotonic drink brand Pocari Sweat. As for television advertising variables have a significant influence on the purchase decision variable isotonic drink brand Pocari Sweat. Keywords: Quality Products, television ads and Purchase Decision